TOTAL AND GAS FLOW ACTIVITY OF THE SEYFERT GALAXY NGC3227 NUCLEUS FOR ITS DIFFERENT EVOLUTIONARY EPOCHS - Bikmaev, I. F.; Pronik, I. I.; Sharipov, L. M. (Одеські астрономічні публікації, 2012)
A comparative analysis of time variations of spectral characteristics of the Seyfert galaxy NGC 3227 nucleus: equivalent widths (EW γ), relative intensities, the width of the Balmer line profiles was carried out. Spectral data obtained in April 2009 with the 1.5-m Russian-Turkish telescope (RTT-150) and data published in the literature were used. Results of the comparative analysis showed the weakening of total activity and, consequently, gas flow activity of the galaxy nucleus in the time interval of more than 30 years.